2021
DOI: 10.1155/2021/7394699
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Levels of HCY, MIF, and hs-CRP Correlate with Glycolipid Metabolism in Adults with Never-Medicated First-Episode Schizophrenia

Abstract: Objective. It has been reported that the prevalence of metabolic syndrome (MS) in multiepisode patients with schizophrenia is 35.3%, which is 2- to 4-fold higher than in the general population. The study is designed to compare the glycolipid metabolism in patients with first-episode schizophrenia (FES) with sex- and age-matched healthy controls to investigate changes in serum levels of homocysteine (Hcy), macrophage migration inhibitory factor (MIF), and high-sensitive C-reactive protein (hs-CRP) and their rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Although the results are the same as previously reported [50], there are nevertheless many reports of varying results, suggesting that Hcy concentrations correlated with BMI in patients with schizophrenia [24,51]. The Hcy levels were closely associated with elderly males, obesity, uric acid content, glycolipid metabolism, and metabolic syndromes [42,44,52], whereas our study subjects were on average young and unmedicated, mitigating the effects of confounding factors on Hcy levels, so the results may be more accurate.…”
Section: Discussionsupporting
confidence: 84%
“…Although the results are the same as previously reported [50], there are nevertheless many reports of varying results, suggesting that Hcy concentrations correlated with BMI in patients with schizophrenia [24,51]. The Hcy levels were closely associated with elderly males, obesity, uric acid content, glycolipid metabolism, and metabolic syndromes [42,44,52], whereas our study subjects were on average young and unmedicated, mitigating the effects of confounding factors on Hcy levels, so the results may be more accurate.…”
Section: Discussionsupporting
confidence: 84%
“…Studies consistently demonstrate significantly elevated hsCRP levels in individuals with IGT, with a strong association between increased hsCRP levels and the presence of IGT. 30 This finding supports the concept that chronic low-grade inflammation is a risk factor for the development of T2DM. Similar results have been reported by Simental-Mendia et al, who found an association between elevated hsCRP levels and prediabetes.…”
Section: Discussionsupporting
confidence: 83%
“…Although the results are the same as previously reported [ 55 ], there are nevertheless many reports of varying results, suggesting that Hcy concentrations correlated with BMI in patients with schizophrenia [ 26 , 56 ]. The Hcy levels were closely associated with elderly males, obesity, uric acid content, glycolipid metabolism, and metabolic syndromes [ 31 , 48 , 57 ], whereas our study subjects were on average young and unmedicated, mitigating the effects of confounding factors on Hcy levels, so the results may be more accurate.…”
Section: Discussionmentioning
confidence: 99%